Insights into tail-belting by wild mice encourages fresh perspectives on physiological mechanisms that safeguard mammal tissues from freezing - Rafal Stryjek; Michael H. Parsons; Piotr Bebas (Scientific Reports)
Abstract We investigated tail-belting (TB), the newly-discovered freeze avoidance behavior among wild rodents. When temperatures dropped to -6 °C, wild mice (Apodemus agrarius and Apodemus flavicollis) were observed curling their tails inward and positioning it on the back. A literature search suggested TB had never been documented, presumably because rodents, especially in the laboratory, are seldomly assayed under cold stress. Due to the infrequent occurrence of the behavior, we used infrared and thermal cameras to confirm observations. We also collected tail-skin samples to investigate whether any physiological mechanisms might co-occur with TB. If such mechanisms were found, they could inform wider debate involving freeze protection among mammals, and could potentially lead to understanding mammal susceptibility or resilience to sudden temperature changes such as those associated with climate change. Lastly, we scored behaviors by bank voles (Myodes glareolus) which unexpectedly visited chambers. Across four winters, we observed TB in both Apodemus species during subzero conditions, but bank voles never performed the behavior. We also confirmed that TB occurs as an adaptive reflex which warms the tail. From tissue samples, we found that free amino acids, peptides, and glycoproteins were significantly higher during cold-stress. Thus, TB may have been accompanied by the expression of cold-protective proteins which ostensibly enable the peripheral body parts of mammals to survive temperatures well below 0 °C. These findings should inspire new dialogue regarding the role of lipids in tissues of peripheral organs in mammals. By extension, our findings may lead to the discovery of a putative cryoprotection mechanism among mammals.